Vibrio vulnificus Septicemia after Handling Tilapia Species Fish: A Canadian Case Report and Review - Donald C Vinh; Samira Mubareka; Bunmi Fatoye; Pierre Plourde; Pamela Orr (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Vibrio vulnificus can cause a necrotizing soft tissue infection or primary septicemia; these infections are collectively known as vibriosis. This bacterium is commonly found within molluscan shellfish. Primary septicemia is often fatal, principally affecting persons with chronic liver disease.